Evaluation of antioxidant and antibacterial activities of fish protein hydrolysate produced from Malaysian fish sausage (Keropok Lekor) by-products by indigenous Lactobacillus casei fermentation - Abd Rashid, Nur Yuhasliza; Abdul Manan, Musaalbakri; Pa'ee, Khairul Faizal; Saari, Nazamid; Faizal Wong, Fadzlie Wong (Elsevier, 2022)
Malaysian fish sausage, Keropok Lekor (KL), is a popular fish snack in Malaysia. The fish by-products (FBPs) from KL processing comprise a significant quantity of proteins with high nutritional value. However, in Malaysia, such FBPs are either disposed of into waterways, which may cause environmental pollution, or are processed into products of low economic value, such as fertiliser and animal feed. To maximise the potential of FBPs, a microbial fermentation approach can be used to convert FBPs into bioactive fish protein hydrolysate (FPH). Bioactive FPH has higher economic value due to its potential as a bio-ingredient in the nutraceutical and functional food industries. This study aimed to evaluate antioxidant and antibacterial activities of FPHs from FBPs of KL processing produced by four indigenous Lactobacillus casei strains (LC216, LC217, LC219, and LC220). The relationship between the level and composition of free amino acids during fermentation and the antioxidant and antibacterial activities of the produced FPH was evaluated. The results showed that the FPHs produced using the four L. casei strains had higher 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities (82.8–88.4%) than that of the unfermented FBPs (78.9%). The obtained half-maximal effective concentrations (EC50) of the FPHs were also significantly lower (p < 0.05) than those of the unfermented FBPs. The ferrous chelating ability of the FPHs produced using strain LC217 improved by 68.43% compared to that of the unfermented FBPs. Furthermore, compared to the unfermented FBPs, the FPHs produced using strains LC216 and LC217 had a significantly higher (p < 0.05) maximum growth inhibition against Listeria monocytogenes, Salmonella typhimurium, Escherichia coli and Listeria innocua. Moreover, there was a positive relationship between the degree of hydrolysis and the bioactivities. A strong positive correlation also existed between the level of antioxidant amino acids content and antioxidant activity. Overall, the L. casei fermentative production of bioactive FPHs from the FBPs from KL processing represents an effective, environmentally sustainable and economical strategy for producing bioactive bioingredients, which can be used in functional food production and food preservation.